Pan Overhaul Long Overdue Says Culture Minister - Nero, Sean (Trinidad Guardian)
Speaking at the Laventille Steelband Management Workshop held at the Glass Room Angostura Complex, Culture Minister Singh stated that reforms in the National Panorama competition and pan itself were long overdue.
Keywords: Pan Trinbago (Organization); Steel bands (Music) -- Administration -- Trinidad and Tobago; Workshops (Adult education) -- Trinidad and Tobago